The glamorization of overwork - an empirical study of causes and perceptions of excessive work attitudes in the pursuit of managerial careers - Mira Sophia Ulz (Junior Management Science (JUMS), 2023)
Excessive work behavior remains an issue in pursuing managerial careers. In this context, the glamorization of overwork takes on a crucial role, meaning that unhealthy work behavior is often falsely portrayed in a positive light. This paper provides an overview of influencing factors stimulating overwork behavior and its glamorization within different settings. Relating thereto, a qualitative research approach in the form of semi-structured open interviews was employed. Building on the main propositions of the Job Demands-Resources model (JD-R), this paper finds that individuals are inclined to mirror the behavior of others. In addition, job demands emerging on multiple levels and personality-related intrinsic factors have significant explanatory power for the development of overwork tendencies. The empirical results further reveal that the level of perceived familiarity and trust plays a decisive role in whether individuals are prone to glamorize unhealthy work attitudes. In both professional and non-professional environments, low to medium perceived levels of familiarity and trust in combination with certain stimuli appear to spark the active emphasis on excessive work behavior or the neutralization of strain. In turn, in high-trust settings, this cannot be observed.
Keywords: 650; Workaholism; Overwork; Work engagement; Job Demands-Resources model